Utilização de escória de aciaria na fabricação de blocos de concreto - Benittez, Leandro Henrique (2020)
In this work, the technical feasibility of concrete blocks without structural function is studied, when using BSSF steel slag in its manufacture. In 2019, Brazilian steel production was 32.46 million tons and the world steel 1.87 billion tons and steel slag of 4.54 and 262 million tons, respectively. The incorporation of this waste from the steel industry, in concrete blocks, contributes in a sustainable way to the final destination of an environmental liability. Partial substitutions of 20, 40, 60, 80% of the natural aggregates were made by artificial in the production of the blocks. Initially, tests were carried out to characterize the aggregates and binder. The concrete blocks were manufactured in a cement artifact industry to obtain results at scale, with industrial reality. Then, the blocks were tested for dimensional analysis, water absorption, liquid area and resistance to compression at 28 days of age. The results showed that it is technically feasible to incorporate BSSF steel slag into concrete blocks, since all the blocks produced met the normative requirements. It is noteworthy that the blocks with the replacement of 60% of aggregates were the ones that presented the best results.